Segmentation in touristic sector: LGBT tourists of Sao Paulo - Azevedo, Maurício Sanitá; Martins, Cibele Barsalini; Pizzinatto, Nádia Kassouf; Farah, Osvaldo Elias (Revista de Administração da UFSM, 2012)
The objective of this article is to present the tourism segment LGBT (Lesbian, Gays, Bisexual and Transgender) of Sao Paulo city and gather information about his profile as important support for the tourism sector in defining their marketing strategies. It was carried out an exploratory and statistical data from government and representatives of this public for a description and analysis of data on the composition and profile of this segment, as well as the strategies being used by companies to captivate it and loyalty it. It also composes a Descriptive Study carried out by the Tourism Observatory of São Paulo next to the participants of the Sao Paulo Gay Parade in 2011. As results, it appears that LGBT public presents behavioral particularities as buyers of tourist products, providing during their stay, higher investments than others tourism segments, because it comes as a tourist for a longer period of stay in Sao Paulo, thus leaving more financial resources in the city. It also presents as results, examples of effective use of differentiation strategies by organizations, attraction, service and loyalty in this segment.